Molecular cloning of feline immunodeficiency virus. - Olmsted, R A (1989)
Feline immunodeficiency virus (FIV) is a T-lymphotropic retrovirus associated with immunodeficiency and opportunistic infections in cats. The discovery of FIV provides an opportunity for the development of a small animal model for AIDS. To initiate the molecular and biological characterization of FIV, cDNA clones were synthesized and used to isolate a proviral clone of FIV. Molecular cross-hybridization analysis of FIV with five lentiviruses revealed that nucleotide-sequence similarities exist between FIV and these lentiviruses in the gag-pol genes. However, nucleotide-sequence similarities were not seen upon comparison of the FIV long terminal repeat sequence with known viral sequences. Common antigenic determinants appeared to be shared by FIV, caprine arthritis encephalitis virus, and visna virus as shown by serological cross-reactivity of rabbit antibodies to caprine arthritis encephalitis virus and visna virus with the putative FIV core protein p28. These studies demonstrated that FIV is a member of the lentivirus subfamily and is distantly related to the AIDS lentiviruses of primates. Importantly, progeny virions of our molecular clone were infectious for experimentally inoculated cats. The availability of an infectious molecular clone will make possible a detailed dissection of the molecular pathogenesis of FIV, which may facilitate the development of vaccine and therapeutic strategies for AIDS.